Model Konteks Input Proses Produk dalam Evaluasi Pendidikan - Eko Budi Prasetyo (Dinamika Pendidikan, 2008)
Contexttual  learning, and others represent the innovation  idea which is looked into can fU(fill the requirement  will the make-up of quality tnstruction:  Various effort innovate the instruction  more emphasizing in course (~linteraction  activity. But, in the case of how teaming evaluation relevant not yet careful exhaustively.  Model the evaluation / assessment by tes, especially  objective  tes which. during  the time have so dominant  in practice assessment  result of learning presumably  critical need and looked for alternative  model the assessment result of learning   oth.er.  One of new evaluation  model peeped out  as the alternative model: Input Context  Process  the Product     Keyword: model of the education evaluation